The transformation of HRM in the Eastern European region and in Hungary - Poór, József (Marketing & Menedzsment, 2019)
In Eastern European countries - including Hungary - the characteristics of modern HRM could only be found in traces under the previous regime. One of the first big challenges the HR departments of transition countries had to face was to cope with the massive layoffs after privatisation. International companies have redrawn the characteristics of the labour market and the HR practice in the former socialist countries. Empirical researches unequivocally confirm that HR has become obviously strategic in international companies. There is no comprehensive management and HR knowledge about the countries in this region. Courses presenting this region are missing from the university education and periodic trainings. The express purpose of this study is to contribute, non-exhaustively, to the further reduction of this lack of knowledge.